Integration soil contact model : A flexible pressure-sinkage method for simulating low speed vehicles with wheels and tracks - Kulju, Sampo; Ala-Ilomäki, Jari (Elsevier, 2025)
An integration soil contact model and a modular terramechanics simulator VieteriSim for vehicles running on wheels and tracks were developed. The presented computational method extends the soil contact model by introducing a user defined pressure-sinkage relationship according to a theoretical function or an experimental data set, a numerical integration of pressure over a contact area with a desired resolution and vector based rolling resistance coefficient calculation. The convergence of the model and the capability of the computational method are demonstrated by simulating a cut-to-length timber forwarder running on a soft terrain with and without bogie tracks.
Keywords: vehicle-terrain interaction; physics-based simulation; wheel; tracks; pressure-sinkage; rolling resistance coefficient